The Mediation Role of Profitability on the Effect of Firm Size and Capital Structure Against Automotive Company Values in Indonesia - Najmatus Zahiroh; Budiyanto Budiyanto; Djawoto Djawoto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aimed to investigate and analyze the effects of firm size on profitability, capital structure on the profitability of firm value, the firm size on firm value, and capital structure on firm value. This study also examined whether profitability can mediate the effect of firm size on firm value and whether profitability can mediate the effect of structure on firm value. The population in the study were manufacturing companies in the Automotive and Components sector listed on the Indonesian Stock Exchange (IDX) for 2013-2019. The sample selection was carried out by a saturated sampling method using certain criteria to obtain seven companies as samples. The manufacturing company was chosen because it is one of the sectors experiencing rapid development in Indonesia. The data analysis method used multiple linear regression analysis with Statistical Product and Service Solutions (SPSS) and Sobel Test. Based on the classical assumption test result through the normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, and Sobel Test, this study indicated that all variables did not violate the specified conditions. While the result of the feasibility test on the model through the F test and the coefficient of determination (R2) test stated that the regression model was feasible to use in this study. The result showed that firm size had a significant and positive effect on profitability; the capital structure had a significant and positive effect on profitability, profitability had no significant effect on firm value, firm size had no significant effect on firm value, the capital structure had no significant effect on firm value. In addition, the profitability variables did not mediate capital structure on firm value.